2016
DOI: 10.1080/10749357.2015.1122264
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Peripheral Electrical Stimulation on Corticomuscular Functional Connectivity Stroke Survivors

Abstract: Our results demonstrated that EEG-EMG coherence can detect ES-induced changes in the neuromuscular system. Also, because gamma coherence is linked to afferent inputs encoding, improvement in motor performance is likely related to ES-elicited strong sensory input and enhanced sensorimotor integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 44 publications
4
62
0
Order By: Relevance
“…Moreover, motor control, as measured by the percentage of force deviation in maintaining a steady force output, was also improved after cutaneous electrical stimulation 13. Studies have found that Uni‐TENS augments the effects of TOT in subjects with stroke 4, 5, 51.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, motor control, as measured by the percentage of force deviation in maintaining a steady force output, was also improved after cutaneous electrical stimulation 13. Studies have found that Uni‐TENS augments the effects of TOT in subjects with stroke 4, 5, 51.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism that underlies the improved motor function in paretic limbs after TENS treatment is multifactorial; it involves alleviation of the hyperexcitability of alpha motor neurons,9, 11 reduction of intracortical inhibition,12 and enhancement of corticomuscular functional connectivity 13. Several clinical studies have demonstrated that the hyperexcitability of the alpha motor neurons that innervate the spastic ankle plantarflexor could be reduced by an increase in presynaptic inhibition after repetitive TENS 9, 11.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations